Factors influencing adoption of high tunnels for tomato production in northeast district, Botswana - Badimo, Dandy (International Journal of Agricultural Research, Innovation and Technology, 2021)
The study was carried out to investigate constraints and determinants of high tunnels adoption for tomato production in the North-East District of Botswana, using household survey data sourced directly from 116 horticultural farmers during the months of May and June 2017. Descriptive statistics and a binary probit regression model were employed to analyze constraints and determinants of high tunnels adoption for tomato production. The prohibitive cost of high tunnels, inadequate knowledge on high tunnels, inadequate capital and markets were identified as major constraints that hinder high tunnels adoption. The adoption of high tunnels was found to be positively influenced by years of education, access to extension services and farm size. The findings suggest that encouraging tunnel designers to consider constructing the structure using local materials could be ideal to cut down on the startup cost. Strengthening extension service and re-engineering of the current extension system is necessary to improve the adoption rate of the technology. Int. J. Agril. Res. Innov. Tech. 10(2): 100-109, December 2020